Pengaruh Kepemimpinan Transformasional, Kualitas Kerja Karyawan Terhadap Loyalitas Karyawan dimediasi Kepuasan Karyawan - Nefita, Shela Dhea; Muafi, Muafi; Suhartini, Suhartini (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research is aimed at testing whether there is an influence of Transformational Leadership, Employee Work Quality on Employee Loyalty which is mediated by Employee Satisfaction at CV. Tempo Gelato. This research was conducted at CV. Tempo Gelato. This research uses quantitative methods by taking the entire population (census) and using questionnaires as a measurement tool. The sample from this research is the same as the population, namely 70 CV employees. Tempo Gelato. Hypothesis testing in this study used Smart PLS version 3.2.9. The findings obtained in this research prove that leadership, employee work quality, and employee satisfaction have an important role in employee loyalty at CV. Tempo Gelato